Simulations of hypertrophied heart’s hemodynamics - Grygoryan, R.D.; Aksenova, T.V. (PROBLEMS IN PROGRAMMING, 2018)
The paper describes the modeling technology and the main results of the simulation of hemodynamic effects of cardiac hypertrophy (HH), conducted using previously published mathematical model (MM) [9]. The dynamics of hemodynamic abnormalities are not modeled. MM simulates changes in the central hemodynamics at different degrees and forms of myocardial hypertrophy (MH). Software technology provides a simulation of three types of HH: a) adaptive HH arising in response to the chronic lack of the systemic circulation; b) abnormal HH, which is at the extreme stage of adaptive HH; c) abnormal MH of left ventricle. The first two versions of HH have been simulated by increasing of myocardium’s stiffness, while the third version of HH is simulated via additional decrease of the unstressed volume of the left ventricle. For each version of HH a compensatory potential of self-regulation mechanisms (model uncontrolled cardiovascular system) is studied, and then similar opportunities of baroreflex regulators of hemodynamics have been evaluated. HM satisfactorily reproduces the main changes in blood pressure, cardiac output, and heart rate. The likely role of cell energy mechanisms in the cardiovascular system adaptation to high loads is discussed. The simulator is an autonomous program which can be both a tool to support the medical-physiological research and an educational means for demonstrating causal relationships to medical students. An implementation of the program in a more general program-modeling complex focused on the identification of patterns of functioning of super-human energy is planned.Problems in programming 2016; 2-3: 254-263